2019
DOI: 10.1002/acr.23780
|View full text |Cite
|
Sign up to set email alerts
|

Using Physical Activity Trackers in Arthritis Self‐Management: A Qualitative Study of Patient and Rehabilitation Professional Perspectives

Abstract: Objective. To compare and contrast the perspectives of patients with arthritis and those of rehabilitation professionals regarding starting and sustaining use of physical activity trackers (PATs).Methods. We conducted focus group sessions with patients, physiotherapists, and occupational therapists in Ontario, Alberta, or British Columbia, Canada. To be eligible, patients must have self-reported a diagnosis of inflammatory or osteoarthritis. Rehabilitation professionals reported that at least 40% of their case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(51 citation statements)
references
References 43 publications
4
47
0
Order By: Relevance
“…Finally, this study demonstrated the feasibility of wearing a mobile device over 3 months in patients with inflammatory joint disease. Although patients with inflammatory joint disease may encounter difficulties that are specific to their disease (eg, to handle the device may be difficult because of hand arthritis) [ 49 ], patients wore the device 88% of the days, and many were considering pursuing its use. This study indicates that there are no specific barriers linked to RA or axSpA for using activity trackers.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study demonstrated the feasibility of wearing a mobile device over 3 months in patients with inflammatory joint disease. Although patients with inflammatory joint disease may encounter difficulties that are specific to their disease (eg, to handle the device may be difficult because of hand arthritis) [ 49 ], patients wore the device 88% of the days, and many were considering pursuing its use. This study indicates that there are no specific barriers linked to RA or axSpA for using activity trackers.…”
Section: Discussionmentioning
confidence: 99%
“…Health data obtained from wearables, when combined with sophisticated machine learning algorithms, have helped develop predictive models that can greatly improve health delivery [ 25 - 27 ]. If effectively used, wearables can greatly help in the management of several conditions including rheumatic and musculoskeletal diseases [ 28 , 29 ], chronic pain management [ 30 ], and cardiovascular problems [ 31 ]. To effectively realize the potential benefits of wearable health care devices, a solid understanding of the factors related to their adoption and use is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, often GPs are the first health professionals to interact with many wearable device users. Some studies have investigated health professionals' attitudes toward technologies that are specific to chronic health conditions, such as epilepsy [28], asthma [29], arthritis [30], and other chronic diseases [31]. Another body of literature on GPs' perspectives has examined their experience with a wide array of eHealth innovations, beyond the specific use of wearables [32].…”
Section: Introductionmentioning
confidence: 99%